2013
DOI: 10.1111/spc3.12030
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising the Moral Nature of Emotions in Decision Making: The Case of Shame and Guilt

Abstract: Emotions play a crucial role in moral behavior. The present paper does not contest this point but argues that qualifications of certain feelings such as shame and guilt as moral emotions should not exclusively be based on a proximal analysis of their function. A proximal analysis details how moral emotions produce moral behavior. Emotions are qualified as moral when they are elicited by concerns for others rather than the self and produce prosocial action tendencies. Although researchers have acknowledged that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 59 publications
(81 reference statements)
2
37
0
Order By: Relevance
“…Both in our theorising and in our experiments, we have focussed upon experiences of shame. Although people's general tendency to experience shame, also called shame-proneness (Tangney, 1991), is related to one's actual shame experience (state shame), it does not always have similar consequences (see De Hooge et al, 2008;Nelissen, Breugelmans, & Zeelenberg, 2013). Shame-proneness has been related to negative aspects such as depression, shyness, anxiety, and anger, and it therefore remains to be seen whether shame-prone people would also opt for social approach when provided with the opportunity of situation choice.…”
Section: Discussionmentioning
confidence: 99%
“…Both in our theorising and in our experiments, we have focussed upon experiences of shame. Although people's general tendency to experience shame, also called shame-proneness (Tangney, 1991), is related to one's actual shame experience (state shame), it does not always have similar consequences (see De Hooge et al, 2008;Nelissen, Breugelmans, & Zeelenberg, 2013). Shame-proneness has been related to negative aspects such as depression, shyness, anxiety, and anger, and it therefore remains to be seen whether shame-prone people would also opt for social approach when provided with the opportunity of situation choice.…”
Section: Discussionmentioning
confidence: 99%
“…Tangney suggests that partialling shame from guilt gives the researcher a measure of "shame-free guilt" which she contends is a more pure measure of the guilt construct [42]. However, many authors disagree with this partialling technique [51][52][53][54]. Further, guilt, as measured by the TOSCA, has been shown to be positively related to several measures of adaptive functioning.…”
Section: Guilt and Shame Measurement And Correlatesmentioning
confidence: 99%
“…The functionalist perspective of guilt and shame is built on evolutionary and developmental theory [54,79]. Hutcherson and Gross state that the functionalist perspective "argues that emotions are adaptive solutions comprising a coordinated set of appraisals, communicative gestures, physiological responses, and action tendencies tailored to respond to crucial problems faced by our species over the millennia" [80] (p. 720).…”
Section: Functionalist Perspective On Guilt and Shamementioning
confidence: 99%
See 1 more Smart Citation
“…Shame calls for others (either real or imagined) to forget what was done, whereas guilt asks others to forgive. Although most empirical evidence, largely from the Western world, has supported Lewis's definition of these two self-conscious emotions as substantially different in the manner in which they are felt (Tangney et al, 1996;Wicker et al, 1983), evidence of undifferentiation also exists (Nelissen, Breugelmans, & Zeelenberg, 2013;Smith & Ellsworth, 1985;1987). For instance, Wicker and colleagues (1983) found that differences in the ratings of the two emotions on several phenomenological dimensions were mostly of magnitude rather than of valence.…”
mentioning
confidence: 99%